Development of Running Assistive Technology to Improve Mobility of Blind People: A Systematic Literature Review (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Blind people often face barriers to access information, reducing their ability to participate fully in daily activities such as education, employment, finances, communication, recreation, and independence. This research used the Systematic Literature Review (SLR) method to investigate developments in the use of assistive technology aimed at improving the mobility of people with visual impairments, especially in the context of runners. This study followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were collected from Google Scholar with the help of Harzing's Publish or Perish application. Of the 67 international journal articles downloaded, strict selection was carried out through inclusion and exclusion stages in accordance with established criteria, resulting in 6 journal articles that were relevant to the focus of this research. This study provided a systematic overview of the development of assistive technology to improve the mobility and independence of blind runners. Various technological innovations are discussed in this research, including electromagnetic navigation systems, mechatronics, navigation for marathons, smartphone applications (SPAs), and devices such as EyeVista. The research results conclude that these technologies have great potential to improve mobility and independence of blind people, especially in physical activities such as running. These innovations help individuals navigate complex environments, avoid obstacles, and participate in running with more confidence and independence. Although there are challenges that need to be overcome, the potential of this technology is significant in supporting individuals to achieve a full independence and active participation. It is recommended to continue the research and development of the technology as well as increasing the collaboration among developers, researchers, and visually impaired communities, especially runners, to ensure more effective and widely accepted solutions.